African social concept of beauty: its relevancy to literary criticism - Matiza, Vimbai M. (Leena and Luna International, 2016)
The article seeks to bring out the idea of African social concept of beauty and how it informs the canon of literary criticism. It is at pains to analyse how the beauty of an African person or social group enlightens African and Diasporan critics in literary criticism. The concept of beauty is relative; it is related to the prevailing culture which is perpetuated by print and visual media. By beauty, the article is going to look at various attributes which results in the beauty of a person. Say for example there is internal and external beauty of a person. This beauty is viewed differently by different people but the bottom line is that what matters most? The paper therefore is going to deduce if that concept of beauty has managed to guide these works in as far as literature is concerned. Rather form and content of the works from an African perspective are going to be analysed to find out how much have they taken or they have been informed by this concept.